The people's agents and the battle to protect the American public special interests, government, and threats to health, safety and the environment - Steinzor, Rena.; Shapiro, Sidney A., 1947- (Chicago, [Ill.] ; London : University of Chicago Press, 2010)
Reasonable people disagree about the reach of the federal government, but there is near-universal consensus that it should protect Americans from such dangers as bacteria-infested food and unsafe toys. However, the agencies that shoulder these responsibilities are in chaos. This book explores this dire state of affairs.
Specialized.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Public safety -- United States; Public interest -- United States; Government accountability -- United States; Administrative agencies -- United States; Society; United States of America, USA; Social welfare & social services; Public administration; Jurisprudence & general issues